Manga Vision Cultural and Communicative Perspectives - Pasfield-Neofitou, Sarah; Sell, Cathy (Cultural Studies, 2016)
Manga Vision examines cultural and communicative aspects of Japanese comics, drawing together scholars from Japan, Australia and Europe working in areas as diverse as cultural studies, linguistics, education, music, art, anthropology, and translation, to explore the influence of manga in Japan and worldwide via translation, OEL manga and fan engagement. This volume includes a mix of theoretical, methodological, empirical and professional practice-based chapters, examining manga from both academic and artistic perspectives. Manga Vision also provides the reader with a multimedia experience, featuring original artwork by Australian manga artist Queenie Chan, cosplay photographs, and an online supplement offering musical compositions inspired by manga, and downloadable manga-related teaching resources.